Assessment of periodontal non-surgical treatment performed by general dentists and specialists in periodontics - Luciana de Rezende Pinto; Joni Augusto Cirelli (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate the behavior of general dental practitioners (GP) and dentists with complementary training in Periodontics (CTP) as to the need of accomplishment of this procedure. A questionnaire was applied to 130 professionals, 29 were returned not completed and then, eliminated of the sample. The results demonstrated that 97% of the CTP professionals performed probing during periodontal evaluation and 49% of the GP do not employ it. Most professionals of both groups provide oral hygiene instructions (92% GP and 91% CTP) and supra and subgingival root planning (72% GP and 91% CTP). The basic periodontal therapy is performed before the restorative treatment by 86% of the GP and 97% of the CTP. As to the period on which periodontal reevaluation was achieved after treatment, 33% of the GP performed this procedure in less than 30 days, from which 65% employed a periodontal probe. In the CTP group, 60% reevaluated the patient after 30 to 45 days and 100% used periodontal probe in this procedure. It is concluded that even though the basic periodontal therapy is properly performed by most professionals, the utilization of a periodontal probe as a diagnostic mean for periodontal diseases is neglected.